IRF4 Activity Is Required in Established Plasma Cells to Regulate Gene Transcription and Mitochondrial Homeostasis - Michael Sze Yuan Low (Cell Reports, 2019)
Summary: The transcription factor interferon regulatory factor 4 (IRF4) is critical for the development, maintenance, and function of plasma cells. The mechanism by which IRF4 exerts its action in mature plasma cells has been elusive due to the death of all such cells upon IRF4 loss. While we identify apoptosis as a critical pathway for the death of plasma cells caused by IRF4 loss, we also determine that IRF4 did not regulate the intrinsic apoptotic pathway directly. By using an inducible IRF4 deletion system in the presence of the overexpression of anti-apoptotic BCL2, we identify genes whose expression is coordinated by IRF4 and that in turn specify plasma cell identity and mitochondrial homeostasis. : Plasma cells can provide lifelong immunity by the continued production of high-affinity, antigen-specific antibody. Low et al. reveal that the transcription factor IRF4 acts within established plasma cells to prevent apoptosis and maintain cellular identity and mitochondrial homeostasis. Keywords: antibody, metabolism, gene expression, myeloma, cell survival, humoral immunity, BLIMP1